2022
DOI: 10.1038/s41598-022-18607-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and proapoptotic effects of inhaling gasoline fumes on the lung and ameliorative effects of fenugreek seeds

Abstract: Impacts of inhaling gasoline fumes on the lungs of adult male rats and the alleviating role of fenugreek seeds were evaluated. Twenty-four rats were divided into four groups, unexposed control and fenugreek groups, gasoline exposed groups for 6 h/6 day/week for 10 weeks with and without supplementation of fenugreek seed powder in food (5% w/w). Rats exposed to gasoline fumes showed significant elevation in lung tumor necrosis factor-α, as an inflammatory marker, and the proapoptotic marker Bax with a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
(43 reference statements)
0
6
0
1
Order By: Relevance
“…In contrast, the groups treated with the polyherbal recipe showed nearly normal tissue architecture, with only a few instances of mild congested vessels, slight peribronchiolar infiltration, mild inflammatory cell infiltration in intra-alveolar spaces, and focal hemorrhagic areas. Additionally, mild necrosis of alveolar ducts was observed, suggesting a decrease in inflammation 50,100,101 .…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the groups treated with the polyherbal recipe showed nearly normal tissue architecture, with only a few instances of mild congested vessels, slight peribronchiolar infiltration, mild inflammatory cell infiltration in intra-alveolar spaces, and focal hemorrhagic areas. Additionally, mild necrosis of alveolar ducts was observed, suggesting a decrease in inflammation 50,100,101 .…”
Section: Discussionmentioning
confidence: 98%
“…Still, little attention has been paid to this issue, and so far, only few publications have described the protective activity of some natural agents. Abdrabouh [9,10] has recently reported that rats exposed to gasoline fumes for 6 h daily, 6 days a week for 10 weeks, displayed marked pathological changes in the liver [9] and the lungs [10]. This was manifested by elevated levels of liver enzymes in the blood [9] and oxidative stress and inflammatory markers in tissue homogenates [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Abdrabouh [9,10] has recently reported that rats exposed to gasoline fumes for 6 h daily, 6 days a week for 10 weeks, displayed marked pathological changes in the liver [9] and the lungs [10]. This was manifested by elevated levels of liver enzymes in the blood [9] and oxidative stress and inflammatory markers in tissue homogenates [9,10]. These changes were alleviated by adding fenugreek seed powder (5%, w/w) to a standard diet [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se encontró, que más del 87% de la población involucrada en esta actividad son de sexo masculino, predominantemente son adultos jóvenes (18-40 años), menos del 35% han alcanzado el bachillerato, solo la mitad tiene acceso a servicios de salud y, han estado expuestos constantemente por más de 5 años a estos materiales. Luego, es evidente, que de acuerdo con lo descrito en la literatura sobre el efecto deletéreo que eventualmente tendrán estos compuestos (14)(15)(16)(17) , no solo sobre la función pulmonar sino otros sistemas, aparecerán años después, cuando aumente la exposición acumulada, aparición de comorbilidades y se tengan barrera para acceder a servicios oportunos de salud, tanto en prevención primaria como secundaria. La gasolina es un destilado de petróleo que contiene una mezcla variable de al menos 150 -200 alcanos C4 -C12, cicloalcanos, alquenos, e hidrocarburos aromáticos obtenidos por "craqueo" de fracciones pesadas de petróleo crudo en el intervalo de ebullición 40 -225 ° C (104 -437 ° F) (8) .…”
Section: Discussionunclassified